DESULFURISASI BATUBARA DENGAN METODE FLOTASI MENGGUNAKAN GEL LIDAH BUAYA - Kuntaarsa, Abdullah; Subagyo, Purwo (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2020)
Coal is a solid hydrocarbon rock formed from organic deposits, plant remnants in an oxygen-free environment, effects of pressure and heat that lasts very long. Indonesian coal contains very high sulfur pyrite. Very high levels of sulfur in coal cause environmental pollution and damage to combustion tools. The aim of this research is to reduce the sulfur content in coal using the flotation method, using aloe vera gel. Flotation, the process of separating solids that occur due to differences in surface properties and takes place in a system consisting of three phases, namely the gas, liquid and solid phases, with the help of surfactants there will be a separation between the hydrophobic component and the hydrophilic component, where coal which was originally hydrophilic is converted into hydrophobic with the help of surfactants, thus that the sulfur inside can be separated. In this study, aloe vera gel was used as a surfactant which has high saponin levels. The addition of surfactants causes coal components that are less hydrophobic to become more hydrophobic. Based on the research, the more the addition of aloe vera gel in the flotation process, the more sulfur is taken and the optimum amount of aloe vera gel is 300 ml can reduce sulfur by 45.4024%. As for the flow rate, the smaller the flow rate, the longer contact time and the optimum air flow rate is 0.376 L/minute able to absorb 38.7776% sulfur.